UPAYA PENGEMBANGAN INFRASTRUKTUR PULAU JEMUR SEBAGAI OBYEK WISATA DI KABUPATEN ROKAN HILIR - Eka Safitri; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Jemur Island with the beautiful panorama and the potency of Jemur Island has promised can become as a natural tourism but in this case is still not handled optimally because it is still not the availability of infrastructure (such as infrastructure) that can support and be used as natural tourism of the Jemur Island that can be enjoyed by tourists and can improve APBD of Rokan Hilir Regency. The purpose of this research to know the efforts of development infrastructure of Jemur Island as a travel object of Rokan Hilir Regency and factors that inhibit in the conduct of development efforts. Theory in this research is Suwantoro’s theory that the principal elements supporting the development of tourism, tourism object and tourism attraction, tourism infrastructure, tourism facilities, governance or infrastructure and communities or the environment. This research has used descriptive qualitative research method. The data collected through interview, documentation and observation. Result of this research has showed that the infrastructure in Jemur Island still in the development stage and therefore still need cooperation between the department related to continue these activities. The factors that inhibit of effort were the policy of the road infrastructure, mobile phone network and the mobilization of the material to the point of construction.Key Words : infrastructure, tourism, the development of tourism